Digitales forum romanum: un progetto per la ricostruzione storico-scientifica in 3D del Foro Romano - Spadi, Alessia (Umanistica Digitale, 2019)
Digitales forum romanum is a digital public history project promoted and developed by the Winckelmann Institute of the Humboldt University of Berlin, in collaboration with numerous institutions, not only German ones. Starting from the scientific research on the buildings of the Roman Forum, the project intends to reconstruct in 3D the different versions of the site over time, making them accessible via the web. This project is unique in the panorama of similar works. In fact to date it’s the only one that studies the development of the system linked to the Roman Forum across the various ages, rather than focusing on a single historical moment.